The morphological dimension and antioxidant composition of selected indigenous flavouring plants in Bintulu, Sarawak - Yusli, Nurul Aisyah; Saupi, Noorasmah; Abd Razak, Hanisah Kamilah (Persatuan Biologi Gunaan Malaysia, 2023)
The use of plants as food flavourings, commonly known as herbs and spices, serves as natural sources of flavour, altering the taste and aroma of dishes with only a small amount. Beyond flavour, these plants also contribute essential antioxidants crucial for human health by inhibiting free radicals that can lead to various diseases. In Bintulu, Sarawak, Malaysia, locals traditionally consume indigenous flavouring plants primarily for their culinary impact, often overlooking the pharmaceutical value these plants may offer. This study aimed to assess the marketable appearance and antioxidant composition of indigenous food flavouring plants in Bintulu. Bunches of Pangium edule, Premna serratifolia, Pycnarrhena tumefacta, Scorodocarpus borneensis, and Syzygium polyanthum were obtained from the local farmers market and analyzed for morphological dimensions, total phenolic content, free radical scavenging ability (DPPH), and ferric reducing ability (FRAP). The edible portion of the plants ranged from 57.33% to 84.99%, with P. edule exhibiting the largest edible blade. Total phenolic content varied from 343.27 to 3245.67 mg GAE/100 g, with P. serratifolia having the highest value. Premna serratifolia demonstrated the strongest radical scavenging activity, while S. polyanthum exhibited the highest ferric reducing ability. All species exhibited high antioxidant composition (IC50 = 0.10 to 27.6 μg/mL, FRAP = 469.88 to 9272.50 mg TE/100 g), indicating potential medicinal utility. Further studies on anti-nutrients like oxalate and phytate are recommended to complement the obtained data. Additionally, an ethnobotanical study is suggested to document the traditional medicinal uses of these plants alongside their role as flavor enhancers in cooking.